Effects of pandan aqueous extract on physico-chemical properties of normal and waxy rice starches - Pawinee Deetae; Thungpon Klumrat; Warot Nakakitwibool; Atikorn Panya (My University, 2018)
Pandan aqueous extract (PAE) has traditionally been used as a food additive in Southeast Asia to enhance their flavor, color and health benefits. The purpose of this research was to investigate the effects of PAE on physico-chemical properties of normal rice starch (NRS) and waxy rice starch (WRS). Results indicate that addition of PAE significantly ( p < 0.05) affected the physico-chemical properties of rice starches. For pasting properties, PAE significantly increased peak viscosity, breakdown and pasting temperature of NRS, while PAE decreased peak viscosity, breakdown, final viscosity and setback values of WRS. The addition of PAE to NRS and WRS significantly ( p < 0.05) reduced gel hardness and gel adhesiveness by more than 50% compare to native control gels. The gelatinization thermal properties of both NRS and WRS were significantly ( p < 0.05) increased when PAE was included. Only the gelatinization enthalpy of WRS was influence by the PAE. It was concluded that the addition of PAE considerably improved the thermal stability of WRS.
Keywords: Starch gelatinization; Modified starch; Retrogradation (starch); Food composition and properties